How Oliver Olson changed the world - Mills, Claudia (Farrar, Straus and Giroux, 2009)
Afraid he will always be an outsider like ex-planet Pluto, nine-year-old Oliver finally shows his extremely overprotective parents that he is capable of doing great things without their help while his class is studying the solar system.